Using computer simulation in operating room management: impacts on process engineering and performance - Baumgart, André; Zöller, Anja; Denz, Christof; Bender, Hans-Joachim; Heinzl, Armin; Badreddin, Essameddin (40th Annual Hawaii International Conference on System Sciences, 2007, 2007)
Operating rooms are regarded as the most costly hospital facilities. Due to rising costs and decreasing reimbursements, it is necessary to optimize the efficiency of the operating room suite. In this context several strategies have been proposed that optimize patient throughput by redesigning perioperative processes. The successful deployment of effective practices for continuous process improvements in operating rooms can require that operating room management sets targets and monitors improvements throughout all phases of process engineering. Simulation can be used to study the effects of process improvements through novel facilities, technologies and/or strategies. In this paper, we propose a conceptual framework to use computer simulations in different stages of business process management (BPM) lifecycle for operating room management. Additionally, we conduct simulation studies in different stages of the BPM lifecycle.